The Paradoxical Impact of Globalisation on Women’s Political Representation: A Review of Situations In Southeast Asia - NUR AZIZAH (Jurnal Studi Pemerintahan, 2015)
The representation of women in a political system is a good test of its claims to democracy. Although there are some progress, the level of women political representation in Southeast Asian countries is still low. Women activists propose the adoption of gender quotas as a fast track to address this issue, but the implementation find many obstacles. This article base of my research which want to examine the impact of globalisation for women’s political representation in Southeast Asian countries. The discussion begin with the overview of women’s political representation issue and some theoretical framewoks for adressing that issue. It identified that globalisation has positive and negative impacts on women’s representation. On the one hand, it encourages the emergence of a global gender equality regime which influences pattern of women’s political representation among Southeast Asian countries. Yet, on theotherhand, itpromotes neo-liberalism ideology which is “inherently oppose to policy interventionism”and it also promotes liberal democratic practices, which oppose affirmative policy for women, included gender quota in parliament.We concludes that the paradoxical impact of globalisation causes progress for increasing women’s representation in Southeast Asian countries move slowly. The efforts for increasing women’s representation in some Southeast Asian countries have not been supported by governments’ “intervention” policies such as gender quota and social welfare policies. Southeast Asian countries are also trapped in a liberal democracy practice which promotes ‘one person one vote’ (equality of opportunity). Thus, the opposition to affirmative action (equality of result) is so high. Although some Southeast Asian countries have women quota articles, the implementation has been undermined so far.KEYWORDS: Globalisation Impact, Women, Political Representation,Southeast Asia